Integrating Banjarese of The Philosophy of Sasirangan Fabric Into English Language Teaching: A Cultural-Based Language Learning Approach - Haura, Raudhatul (The Future of Education Journal, 2025)
This research explored the integration of Banjar culture, particularly the philosophy behind Sasirangan fabric, into English language teaching through a culture-based approach. In Indonesia, English language education often emphasizes technical aspects such as grammar and vocabulary, which can create a disconnect from real-life language use. By incorporating local cultural elements like Sasirangan, a traditional fabric with deep philosophical values representing diversity, resilience, and cooperation, this research aims to enrich the learning experience and improve students' English proficiency. The research used a qualitative, literature-based approach to analyzed how Sasirangan’s symbolic meanings can enhance speaking, listening, reading, and writing skills. The reserch finds that integrating cultural values from Sasirangan into English teaching not only fosters a deeper understanding of the language but also strengthens intercultural competence, motivating students and increasing their engagement. Despite challenges such as limited resources and teachers' understanding of local culture, the research suggests that the use of culturally relevant materials, like videos and interactive content, can facilitate this integration. Ultimately, this approach supports both language acquisition and cultural appreciation, offering a holistic learning experience.